A história toda. Um bairro de Viana de Lima, em Bragança. 1960-... - Maria Assis da Cruz Fernandes Ferreira (2017)
The present dissertation arises from the interest in questioning the architectural work as a complex material and symbolic construction, which is not exhausted in the synthesis of the project praxis. The set of row houses in Bairro do Toural in Bragança, designed in 1960 by the architect Viana de Lima, is an object of study that lends itself to this broad understanding of the architectural work and allows for a reflection on its diachronic and contextual dimension. Thus, deconstructing them, the research seeks to recognize the complexity of the processes of conception and appropriation of the urban and domestic space in which multiple actors intervene - from the architect to the inhabitants, who take a preponderant role in their home's production.Particular attention is paid to the conceptual, cultural and historical context in which Viana de Lima's project is developed, identifying the main themes of the architectural debate of the 1950s and 1960s, characterized by the search for a modernity of principles and not only of forms, and the way in which these themes influence the architect's design practice in the city of Bragança. On the other hand, we try to understand how the modern architectural proposal was received by the inhabitants of a still rural context, marked by the persistence of cultural practices that testify man's productive relationship with the territory and the strength of family bonds.The observation of the present circumstance through a field work that collects oral, photographic and graphic records serves as a starting point to understand a story of transformations of space, that are the physical expression of the reciprocal relation between architecture and life. Due to their typo-morphological specificity, row houses constitute the framework that allows the comparative analysis of the collected material, as well as the emergence of recurrent spatial themes that allow the identification of practices and ways of actively inhabiting Bairro do Toural.This dissertation seeks to be a comprehensive study of this domestic space, which goes through the troubled process of its production and which identifies and relates the contributions of its various actors. An analysis is made of the coincidences and frictions between the functionalist space designed by Viana de Lima and the daily experience of the inhabitants that assign uses and meaning to the spaces of the house, between the formalization of the project and the informality of the actions that follow, as a way of questioning the limits of the designing practice and the nature of the architectural act.